Optimization on timings of injection and spark of a high compression-ratio stratified-charge methanol engine under ultra-lean burn. (1st February 2021) - Gong, Changming; Zhang, Zilei; Sun, Jingzhen; Liu, Fenghua
Highlights: An ideal stratified-charge mode was proposed for methanol engine ultra-lean burn. Methanol late-injection strategy under high compression ratio was used. Optimal methanol injection and spark timings under ultra-lean burn were studied. Injection and ignition timings determined the rationality of stratified-charge. Optimal injection and ignition timings obtain the best ultra-lean burn performance. Abstract: High compression-ratio and ultra-lean burn are the two most effective measures to enhance economy of spark-ignition engines. The investigations were performed on a high compression-ratio stratified-charge direct-injection spark-ignition methanol engine with an injector of non-uniform spray-line distribution. The effect of timings of injection and spark on the concentration field of the stratified-charge mixture, combustion and emissions behaviors of methanol engine under ultra-lean burn conditions was studied by simulation. Simulation results demonstrated that an ideal stratified-charge mixture was the guarantee to obtain the best performance of a high compression-ratio spark-ignition methanol engine under ultra-lean burn. The timings of injection and spark had a remarkable effects on mixture formation, combustion and emission of a methanol engine under ultra-lean burn. There existed an optimal timings of injection and spark to obtain the peak in-cylinder pressure, peak heat release rate and peak in-cylinder temperature of methanol engine under ultra-lean burn, as well as the shortest ignition delay and combustion duration. Lower CO (carbon monoxide), unburned methanol and soot emissions, and higher NO (nitric oxide) emission were acquired at optimal timings of injection and spark under high compression-ratio and ultra-lean burn. Hence, realizing an ideal stratified-charge combustion was the key to obtain the best performance of a spark-ignition methanol engine under high compression-ratio and ultra-lean burn.